2022
DOI: 10.2147/prbm.s348661
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Psychological Resilience and Mental Health among Newly Graduated Nursing Students: A Latent Profile and Generalized Additive Model Analysis

Abstract: Background Psychological resilience is important to mental health and professional development in newly graduated nursing students (NGNSs). However, the association between psychological resilience and mental health in NGNSs is less explored. Purpose The current study was designed to determine mental health profiles measured by the Kessler 10 scale (K10) and evaluate the non-linear association between psychological resilience and mental health in NGNSs. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…24 This scale has been successfully administered in previous studies. 14 16 The Cronbach's alpha was 0.875 in the present study.…”
Section: -Item Connor-davidson Resilience Scalesupporting
confidence: 49%
“…24 This scale has been successfully administered in previous studies. 14 16 The Cronbach's alpha was 0.875 in the present study.…”
Section: -Item Connor-davidson Resilience Scalesupporting
confidence: 49%
“… 3 In addition, it demonstrated that students who had nursing role models were prone to Flexibility and were more self-adjusted to academic stress than those who did not have nursing role models, which was consistent with our previous studies. 2 , 22 In the pandemic of COVID-19, nursing role models helped nursing students recognize the value and possibilities of nurses, thus changing their negative attitude to the nursing profession. 40 According to Motivational Theory of Role Modeling, nursing role models could inspire and motivate nursing students to achieve professional identification and internalization.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 613 nursing students were approached from Be Resilient to Nursing Career (BRNC) between October and December 2021. 2 , 22 A total of 595 completed the booklet resulting in a response rate of 97.1%. A sample size of 500 provides good test power and convergent validity for the model indicators.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations